IMPLEMENTASI KEBIJAKAN IZIN MENDIRIKAN BANGUNAN (IMB) DI KANTOR PELAYANAN TERPADU SATU PINTU DAN PENANAMAN MODAL (KPTSP & PMD) KABUPATEN MAMUJU UTARA - Darwis, Muhammad (Katalogis, 2015)
The objectives of this research are to determine and analyze the policy implementation of Building Permit at Office ofOne Stop Services and Investment of District Northern Mamuju. Type of this research is qualitative by taking community and officers/staff office of One Stop Services and Investment of District Northern Mamuju as informants which were determined purposively. Data collection methods include participant observation, in-depth interviews, documentation, and triangulation, while data analysis techniques include data reduction, display the data and draw conclusions and verification. The result shows that policy implementation of Building Permit in the District Northern Mamuju is already running, but it is not maximized due to the content of the policy such as the desired degree of change has not been seen since the attitude and behavior ofpeople only acquire the Building Permit if they need it as a requirement of their dealing with bank Lack of socialization causes low knowledge and understanding as well as the public awareness in acquiring of Building Permit. Involved resources have limitedness, both in terms of quality and quantity, while the context implementation (implementation environment) is not maximized due to the low level of compliance with policy targets because of slow and complex service.